Model-model Pengembangan Kurikulum - Ainun, Reski Amelia; Hamzah, Rahma Ashari; Sari, Chelsy Ayunda; Nurfitriana, Shalsa; A, Irfan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze various curriculum development models used in education, particularly the Tyler, Taba, Oliva, and Grass Roots models. Curriculum is a crucial component in the learning process that serves as a guideline for achieving educational objectives. The method used in this study is a literature review by examining various scientific sources such as journals, books, and related articles. The results show that each curriculum development model has its own characteristics, strengths, and weaknesses. The Tyler model emphasizes systematic learning objectives, the Taba model focuses on an inductive approach based on students’ needs, the Oliva model is comprehensive and flexible, while the Grass Roots model highlights the active role of teachers in curriculum development. Therefore, the selection of a curriculum model should be adjusted to students’ needs, school conditions, and current developments to ensure effective and relevant learning.